11x+10-3x+(-7)=-9+2x

Simple and best practice solution for 11x+10-3x+(-7)=-9+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+10-3x+(-7)=-9+2x equation:


Simplifying
11x + 10 + -3x + (-7) = -9 + 2x
11x + 10 + -3x + -7 = -9 + 2x

Reorder the terms:
10 + -7 + 11x + -3x = -9 + 2x

Combine like terms: 10 + -7 = 3
3 + 11x + -3x = -9 + 2x

Combine like terms: 11x + -3x = 8x
3 + 8x = -9 + 2x

Solving
3 + 8x = -9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
3 + 8x + -2x = -9 + 2x + -2x

Combine like terms: 8x + -2x = 6x
3 + 6x = -9 + 2x + -2x

Combine like terms: 2x + -2x = 0
3 + 6x = -9 + 0
3 + 6x = -9

Add '-3' to each side of the equation.
3 + -3 + 6x = -9 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = -9 + -3
6x = -9 + -3

Combine like terms: -9 + -3 = -12
6x = -12

Divide each side by '6'.
x = -2

Simplifying
x = -2

See similar equations:

| 0.6x+14.1=x-7.3 | | 3x(4/2) | | 3(8x+9)-9x=7x+19 | | Y-0=1/4[x-(-4)] | | 14-2(3a+1)=2(3a-2) | | 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 |

Equations solver categories